2006
DOI: 10.1088/0031-9155/52/2/001
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of equivalent dose to organs and tissues of the patient and of the physician in interventional radiology using the Monte Carlo method

Abstract: This study presents the results of computations of organ equivalent doses and effective doses for the patient and the primary physician during an interventional cardiological examination. The simulations were carried out for seven x-ray spectra (between 60 kVp and 120 kVp) using the Monte Carlo code MCNP. The voxel-based whole-body model VIP-Man was employed to represent both the patient and the physician, the former lying on the operation table while the latter standing 15 cm from the patient at about waist l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 17 publications
2
41
0
2
Order By: Relevance
“…These measurements resulted in a normalized dose conversion factor of 0.16 mGy/Gy.cm2 for the left breast, 0.08 mGy/Gy.cm2 for the right breast, and a normalized overall breast dose of 0.12 mGy/Gy.cm2. Breast dose measurements from the literature 1 , 2 , 3 , 4 ranged from 0.03 to 0.12 mGy/Gy.cm2. The findings from this study are in line with the values found in the literature, although the approach of using Gafchromic film to measure breast dose in coronary angiography hasn't been used before.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These measurements resulted in a normalized dose conversion factor of 0.16 mGy/Gy.cm2 for the left breast, 0.08 mGy/Gy.cm2 for the right breast, and a normalized overall breast dose of 0.12 mGy/Gy.cm2. Breast dose measurements from the literature 1 , 2 , 3 , 4 ranged from 0.03 to 0.12 mGy/Gy.cm2. The findings from this study are in line with the values found in the literature, although the approach of using Gafchromic film to measure breast dose in coronary angiography hasn't been used before.…”
Section: Resultsmentioning
confidence: 99%
“…Breast dose measurements can be found in the literature, 1 , 2 , 3 , 4 however these are normally performed using thermoluminescence dosimeter (TLD) or Monte Carlo‐based simulations with neither method expressing individual breast dose nor the breast dose distribution. Radiochromic film has the advantage of providing spatial dose information over point‐dose measurements and was used to assess breast dose distribution in coronary angiography.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups used Monte Carlo methods to simulate the patient doses under IR procedures [22][23][24] . FAX06 and MAX06 phantoms were applied by Kramer et al to calculate organ doses for the most common examinations in X-ray diagnosis [22] .…”
Section: Introductionmentioning
confidence: 99%
“…FAX06 and MAX06 phantoms were applied by Kramer et al to calculate organ doses for the most common examinations in X-ray diagnosis [22] . Bozkurt and Bor used VIP-Man to simulate the organ doses in an interventional cardiological procedure [23] . Garzón et al employed Monte Carlo code with FASH and MASH phantoms to stimulate the organ doses of patients undergoing hepatic chemoembolization procedures [24] .…”
Section: Introductionmentioning
confidence: 99%
“…Voxel phantoms have been developed to satisfy the demand to represent the human anatomy more realistically 7) . Recently Bozkurt et al estimated equivalent dose to organs of the patient and the physician in cardiac catheterization using voxel phantom, VIP-man 8) . However, there was not enough dose assessment data derived from voxel phantoms for interventional procedure.…”
Section: Introductionmentioning
confidence: 99%